Neural specialization of phonological and semantic processing in young children. Issue 11 (28th June 2018) - Weiss, Yael; Cweigenberg, Hannah G.; Booth, James R.
Abstract: This study aimed to examine early specialization of brain regions for phonological and semantic processing of spoken language in young children. Thirty‐five typically developing children aged from 5 to 6 years performed auditory phonological (same sound judgment) and semantic (related meaning judgment) word‐level tasks. Using functional magnetic resonance imaging, we examined specialization within the language network, by conducting three levels of analysis. First, we directly compared activation between tasks and found a greater sound judgment as compared to meaning judgment activation in left superior temporal gyrus (STG) and supramarginal gyrus. In contrast, greater meaning judgment as compared to sound judgment task activation was found in left middle temporal gyrus (MTG). Second, we examined the brain‐behavior correlations and found that phonological skill was correlated with the task difference in activation in left superior temporal sulcus, whereas semantic skill was correlated with the task difference in activation in left MTG. Third, we compared between two experimental conditions within each task and found a parametric effect in left STG for the sound judgment task, and a parametric effect in left MTG for the meaning judgment task. The results of this study indicate that, by the age of 5–6 years, typically developing children already show some specialization of temporo‐parietal brain regions for phonological and semantic processes. However, there were no task differences in the left inferior frontal gyrus suggesting that the frontal cortex may not yet be specialized in this age range, which is consistent with the delayed maturation of the frontal cortex.